2008
DOI: 10.1108/10222529200800005
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of chartered accountants’ awareness and understanding of XBRL

Abstract: eXtensible Business Reporting Language (XBRL) is an important new technology for the electronic communication of business and financial data and, by implication, relevant to, inter alia, chartered accountants. Because research in Australia and the USA showed unacceptably low levels of awareness and understanding of XBRL, research was conducted to determine the levels of awareness and understanding of XBRL in South Africa. The study was limited to chartered accountants. The results showed that the majority of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 8 publications
2
20
1
1
Order By: Relevance
“…For example, a US survey found that only 33% of the American Institute of Certified Public Accountants (AICPA) and US XBRL members have a background in XBRL (Steenkamp and Nel, 2012). In the UK, Dunne et al (2013) found that different stakeholders had a lack of awareness about XBRL, similarly, South Africa has a very low awareness about XBRL (Nel and Steenkamp, 2008). This will hinder XBRL adoption and perceived usefulness (Bovee et al, 2002;Henderson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a US survey found that only 33% of the American Institute of Certified Public Accountants (AICPA) and US XBRL members have a background in XBRL (Steenkamp and Nel, 2012). In the UK, Dunne et al (2013) found that different stakeholders had a lack of awareness about XBRL, similarly, South Africa has a very low awareness about XBRL (Nel and Steenkamp, 2008). This will hinder XBRL adoption and perceived usefulness (Bovee et al, 2002;Henderson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…With XBRL being in the early stage in South Africa, about 89% chartered accountants have never heard about XBRL, and only 17% were not interested in learning more about the format (Nel & Steenkamp, 2008). This unawareness issue is similar to that in the UK where Dunne et al (2009) has found that most of the accountants, tax practitioners and users were not aware of the benefits of the XBRL format.…”
Section: Practitioners" Awareness and Understanding Of Xbrlmentioning
confidence: 98%
“…A body of XBRL literature indicates that businesses have limited knowledge on XBRL and do not realize the benefits of XBRL. These findings appeared in New Zealand (Cordery, Fowler, & Mustafa, 2011), United Kingdom (Dunne, Helliar, Lymer, & Mousa, 2009), South Africa (Nel & Steenkamp, 2008), Jordan (Abed, 2018) German (Felden, 2011), Australia (Indrit & Rao, 2007), USA (Pinsker, 2003), Italy (Rosa & Caserio, 2013), Indonesia (Wulandari & Ali, 2019), and Malaysia (Ilias, Ghani, & Azhar, 2017;Ilias, Razak, & Rahman, 2015). In order to ensure successful implementation of MBRS in Malaysia, there is a need to explore the knowledge of practitioners, their readiness, and their intention to use MBRS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A linguagem XBRL tem o potencial de colaborar para o aumento de transparência das companhias no mercado (McGuire et al, 2006;Nel & Steenkamp, 2008;Bonsón, 2001;Wymeersch, 2008).…”
Section: Considerações Finaisunclassified